2018
DOI: 10.1111/ggi.13517
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation to live better with dementia

Abstract: The goal of dementia treatment is to improve the quality of life for both people with dementia and their families. Rehabilitation as a non‐pharmacological approach, coordinated with pharmacological treatment, aims to allow patients to live better by slowing the progression, and relieving the behavioral and psychological symptoms of dementia. In dementia, the manifestation of symptoms caused by neurological impairment is modified by various factors; thus, multidimensional assessment and approaches are effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…The effects of NPTs were independent of the pathological changes in the brain during disease state causing dementia, therefore NPTs are effective in patients with different subtypes of dementia such as VD and dementia due to AD. This is consistent with the novel concept of NPT, which focuses on each patient's function rather than pathophysiological or neurological causes of their disease 21 . In the present study, we further demonstrated that NPT induced similar changes in the brain activities of patients with either VD or dementia due to AD (see Fig.…”
Section: Brain Region P (Fwe) Ke P (Unc) T X Y Zsupporting
confidence: 85%
See 3 more Smart Citations
“…The effects of NPTs were independent of the pathological changes in the brain during disease state causing dementia, therefore NPTs are effective in patients with different subtypes of dementia such as VD and dementia due to AD. This is consistent with the novel concept of NPT, which focuses on each patient's function rather than pathophysiological or neurological causes of their disease 21 . In the present study, we further demonstrated that NPT induced similar changes in the brain activities of patients with either VD or dementia due to AD (see Fig.…”
Section: Brain Region P (Fwe) Ke P (Unc) T X Y Zsupporting
confidence: 85%
“…This is considered to be the reason why these patients do not respond to pharmacological treatments 5 . This idea is supported by the fact that patients with CIND and MCI show improvements in their cognitive functions after NPTs [18][19][20][21][22][23] , and neuroimaging studies have revealed that these patients still show signs of brain plasticity 16,17 . The present study applied this idea to patients with dementia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While the ability of self‐reflection is preserved, support should be provided to enhance their self‐management ability to be more resilient. However, in advanced stages, a person with dementia might find it difficult to self‐reflect and remain motivated to change their behaviors . In such cases, people around them should provide special consideration so that maladaptive behaviors do not become apparent …”
Section: Introductionmentioning
confidence: 99%